2019
DOI: 10.18331/brj2019.6.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative biohydrogen production from a novel combination of vermicompost as inoculum and mild heat-pretreated fruit and vegetable waste

Abstract: Please cite this article as: Pascualone M.J., Gómez Costa M.B., Dalmasso P.R. Fermentative biohydrogen production from a novel combination of vermicompost as inoculum and mild heat-pretreated fruit and vegetable waste. Keywords: Biohydrogen Dark fermentation Fruit and vegetable waste Vermicompost Mild heat-pretreated substrateThis study reports for the first time on biohydrogen production by dark fermentation using a novel combination of mild heatpretreated fruit and vegetable waste (FVW) as raw material and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…The graph shows that inoculum pre-treatment had a positive effect on hydrogen production. This is consistent with other research ndings [26, [27][28][29][30], which found that chemical and physical pre-treatment of the inoculum enhances hydrogen production. Figure 3 also shows that the different inoculum pre-treatments clearly had a varied effect on hydrogen production.…”
Section: Effect Of Inoculum Pre-treatment On Hydrogen Yieldsupporting
confidence: 93%
See 1 more Smart Citation
“…The graph shows that inoculum pre-treatment had a positive effect on hydrogen production. This is consistent with other research ndings [26, [27][28][29][30], which found that chemical and physical pre-treatment of the inoculum enhances hydrogen production. Figure 3 also shows that the different inoculum pre-treatments clearly had a varied effect on hydrogen production.…”
Section: Effect Of Inoculum Pre-treatment On Hydrogen Yieldsupporting
confidence: 93%
“…Scholars [13,27] agree that inhibition of hydrogen consuming bacteria can be temporary, adding that spore forming hydrogen consuming bacteria can reactivate after a period of time, forming new stable microbial communities that are adapted to the environment. Researchers [29] ,mention that it is also possible for an inoculum pre-treatment to also suppress non-sporing hydrogen producing bacteria while some sporulating hydrogen consuming bacteria (methane producers) manage to survive the harsh pre-treatment conditions. For example, [23] states that suppression of non-spore forming HPB from the genus Enterobacter can occur while sporulating HCB like Clostridium aceticum and Clostridium thermoautotrophicum can withstand pre-treatment.…”
Section: Effect Of Inoculum Pre-treatment On Biogas Composition Over ...mentioning
confidence: 99%
“…Biohydrogen is a clean energy carrier that is a by-product of microorganisms acting on organic biomass [ 126 ]. Bacteria that produce biohydrogen are either photosynthetic, aerobic, or anaerobic [ 127 ]. Bacillus , Enterobacter , Clostridium , Lactobacillus , and Bfidobacterium have been used to produce biohydrogen successfully [ 128 ].…”
Section: Bio-refinery Productsmentioning
confidence: 99%
“…For example, the formation of 86 mM acetate was reported upon dark fermentation of sugar beet molasses by Caldicellulosiruptor saccharolyticus [15]. Likewise, 76-91 % of the metabolites was found to be acetate in the dark fermentation effluent of fruit and vegetable waste [16]. In sequential hydrogen production process where dark fermentation is followed by photofermantation, acetate formed during dark fermentation is further converted into hydrogen by PNS bacteria in photofermentation stage thereby increasing the efficiency of the overall process.…”
Section: C2h4o2 + 2h2o → 2co2 + 4h2 (3)mentioning
confidence: 99%